Responses of crocodilians to construction of a hydro-electric dam on the Madeira river in the Brazilian Amazon - Campos, Zilca M.S.; Muniz, Fábio L.; Mourão, Guilherme; Magnusson, William Ernest (Herpetological Journal, 2020)
The spillways of the Santo Antônio Hydro-electric Dam on the Madeira River in Brazilian Amazonia were closed in November 2011, inundating more than 100 km of river and reducing the annual fluctuations in water level. We surveyed the crocodilians in the affected area for two years before and for eight years after dam filling in order to evaluate the effects of the dam on the size structure of the population, the distribution of each species, and the detectability of individuals to interpret changes in apparent density. Our methodology was probably not appropriate to evaluate trends in population characteristics of Paleosuchus palpebrosus or P. trigonatus, but there was little evidence of an effect of the dam on the numbers of Caiman crocodilus and Melanosuchus niger in the area, and the distributions of all caiman species along the river changed only slightly after the dam was constructed. However, the proportions of small C. crocodilus and large M. niger detected in surveys increased eight years after dam filling. Despite having detectable effects on some population characteristics, the dam does not appear to represent a threat to the persistence of the species in the area if deforestation along the banks of the reservoir can be avoided. © 2020, British Herpetological Society. All rights reserved.
Keywords: Amazonia; Conservation; Crocodilians; Dam; Environmental Impact